Carbapenem-resistant Acinetobacter baumannii: A challenge in the intensive care unit - Jiang, Yuan; Ding, Yinhuan; Wei, Yueshuai; Jian, Chunxia; Liu, Jinbo; Zeng, Zhangrui (Frontiers in Microbiology, 2022)
Carbapenem-resistant Acinetobacter baumannii (CRAB) has become one of the leading causes of healthcare-associated infections globally, particularly in intensive care units (ICUs). Cross-transmission of microorganisms between patients and the environment may play a crucial role in ICU-acquired CRAB colonization and infection. The control and treatment of CRAB infection in ICUs have been recognized as a global challenge because of its multiple-drug resistance. The main concern is that CRAB infections can be disastrous for ICU patients if currently existing limited therapeutic alternatives fail in the future. Therefore, the colonization, infection, transmission, and resistance mechanisms of CRAB in ICUs need to be systematically studied. To provide a basis for prevention and control countermeasures for CRAB infection in ICUs, we present an overview of research on CRAB in ICUs, summarize clinical infections and environmental reservoirs, discuss the drug resistance mechanism and homology of CRAB in ICUs, and evaluate contemporary treatment and control strategies.